Ecological and evolutionary facets of biodiversity. The Second Interdisciplinary Symposium, 28-30 September 2017, Cluj-Napoca, Romania - multiple authors (Studia Universitatis Babeș-Bolyai. Biologia, 2017)
Ecological and evolutionary facets of biodiversity. The Second Interdisciplinary Symposium, 28-30 September 2017, Cluj-Napoca, Romania. BOOK OF ABSTRACTS